Desarrollo de un software para el procesamiento de datos obtenidos de pruebas de inyectividad en campos petroleros (2018)
Monitoring and measuring the parameters of a reservoir are key for the development of an oilfield, those allow the engineer to evaluate and apply actions to improve the production and conditions of the field, this project was created based on the needs to create a monitoring system economic that allow the acquisition of the data and the monitoring of those during and injectivity test. Due to the named facts a data acquisition system was developed based on the interaction of a logic programmable board and a software that allows gather and transfer the data and monitoring in real time a test. The system was validated trough de monitoring of the important parameters on a homologue situation and data was obtained and graphed and an injectivity index calculated. Besides a financial evaluation was complete for the use of the system on injectivity test through the cooperation of a scenario seen by the company against the software created for this project.